Literature Review and Pharmacological Activities of Jeeraka - L. Sreelakshmi; Ch. Sri Durga; K. Satyaprabha (International Journal of Ayurveda and Pharma Research, 2025)
Jeeraka is widely utilized in Ayurvedic therapeutic preparations, both on its own and in combination with other herbs. Acharya Charaka listed it as part of the Shula Prashamana group, while Susruta and Vagbhata classified it under the Pippalyadi Varga. Additionally, Jeeraka is mentioned in the Haritakyadi Varga in Bhavaprakasha Nighantu. It is primarily known for its carminative and digestive properties like Deepana pachana grahi, and it is also employed for various conditions related to the Garbhashaya (uterus), Hrdya (heart), and Netra (eyes), among others. Jeeraka is identified as Cuminum cyminum and belongs to the Umbelliferae family. Materials and methods: Relevant Ayurvedic texts, including the Caraka Samhita, Sushruta Samhita, and various Nighantus, as well as modern literature, research works, and online sources, have been considered. Results: Examined the vernacular names and synonyms of Jeeraka, Nirukthi, and Rasapanchaka, including the therapeutic properties of Jeeraka. Conclusion: Although Jeerka is a spice commonly used in everyday cooking, it also possesses impressive pharmacological properties.